Pengaruh Pemanfaatan Sistim Informasi Akuntansi Berbasis Web Terhadap Kinerja Para Pelaku Bisnis Multi-Level-Marketing (MLM) - Apriana Marselina; Sesilianus Kapa (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
The purpose of this study was to determine the effect of the Utilization of Accounting Information Systems, Social Norms and Conditions that facilitate individual performance on MLM business people at PT Melia Sehat Sejahtra. The contribution to be given by researchers in this study is that the researcher wants to obtain certainty or to prove from theoretical concepts that explain that there is an effect caused by the Utilization of Accounting Information Systems, Social Norms and Conditions that facilitate the improvement of individual performance. This research was conducted using population, companies engaged in the field of Multy-Level-Marketing that have used Web-based Accounting Information Systems. The company that became the sample of researchers was PT. Melia Sehat Sejahtra. This company is one of the companies that uses a Multy-Level-Marketing marketing system and has used a Web-based Accounting Information System. PT employees. Melia Sehat Sejahtra is spread all over Indonesia. To reach respondents, the researchers sent questionnaires using e-mail or electronic mail. The survey results collected will be processed and analyzed using SEM, and the analysis tool used by researchers is Amos. Based on the results of research conducted that the three variables including the Utilization of Information Technology, Social Norms and Conditions that facilitate a significant effect on Individual Performance